Pengaruh Kesadaran Halal, Kualitas Pelayananan Promosi Terhadap Minat Beli Konsumen Padan Martabak Buffet Ahmad Salim Medan - Nurul Fadillah; Ahmad Kholil; Muhammad Zuhirsyan (AGHNIYA : Jurnal Ekonomi Islam, 2021)
This study aims to determine the effect of halal awareness, service quality and individual promotions (partially) as well as together (simultaneously) on consumer buying interest. The data’s type is quantitative, the data sources used are primary and secondary data. The primary data source was obtained through distributing questionnaires to 100 consumers of Martabak Buffet Ahmad Salim Medan stores which were obtained by using nonprobability sampling technique. The method used is a survey method. The questionnaire was assessed with a Likert scale, validity and reliability tests. The prerequisite test includes the Normality Test, Multicollinearity Test and Heteroscedasticity Test. The data analysis method used for testing this study are multiple linear regression analysis, simultaneous test (F test), determination test, and partial test (t test) with a significant level 5 percent (α = 0,05) and the data was processed using software SPSS 22. Based on the partial test, this study showed that the halal awareness negative and has no significant effect with a significance level 0.968, service quality positive and has significant effect with a significance level 0,000, whereas promotion negative and has no significant effect with a significance level 0,50. Simultaneously, halal awareness, service quality and promotions are significantly influence Return on Asset (ROA) with a significance level 0,000.